If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 27 + 24x = 26x + -35 Reorder the terms: 27 + 24x = -35 + 26x Solving 27 + 24x = -35 + 26x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-26x' to each side of the equation. 27 + 24x + -26x = -35 + 26x + -26x Combine like terms: 24x + -26x = -2x 27 + -2x = -35 + 26x + -26x Combine like terms: 26x + -26x = 0 27 + -2x = -35 + 0 27 + -2x = -35 Add '-27' to each side of the equation. 27 + -27 + -2x = -35 + -27 Combine like terms: 27 + -27 = 0 0 + -2x = -35 + -27 -2x = -35 + -27 Combine like terms: -35 + -27 = -62 -2x = -62 Divide each side by '-2'. x = 31 Simplifying x = 31
| -15t^2+90t-120=0 | | -4+x/3=-5 | | -9.5=-38 | | 2v^2+3=0 | | 10x+7=3(3x+7) | | 12345+q-3=999(99+607) | | 23(x-2)=5+4x | | X^2-285=-4x | | y(2+x)=zfory | | 3(4x-7)+7(x+4)=3(x+7)-(x+2) | | 9-4y+3=-10y-25 | | 3x+44=5x+24 | | 6k+10.5=k+18 | | 24y+3=12x-5 | | 8w^2-6w= | | (x^2-x+3)(x+1)= | | 13x-9y=7 | | 5x+44=7x+52 | | 6+14y-3=9y+52-2y | | 2y^2-5x+3y-7=0 | | 9+7x-3-3= | | 6a+3b=0 | | y=x(x+a)(x-b) | | -4x+66=74+-6x | | 378=x^2-3x | | 30x+80=20x+100 | | (-5+2y+u)(-7)= | | 5(x-2)=23-4x | | x+7=2x+18 | | 2x-3+5x=8(3x+5) | | 5n+3n=17+7 | | 3X+5Y+3Z=-22 |